ANALISIS KEBERADAAN PT TEBAR TANDAN TENERAHSAMPOERNA AGRO TBK DALAM MENINGKATKAN PENDAPATAN MASYARAKAT - Anggela Khelsy Alveonari; Aminuyati Aminuyati; F. Y. Khosmas (Universitas Tanjungpura, 2021)
AbstractThis study aims to identify and describe the existence of PT Tebar Tandan TenerahSampoerna Agro Tbk in increasing the income of the people of Sidan Village, Menyuke District, Landak Regency. The method used in this research is qualitative with the type of interactive inquiry. The informants in this study consisted of 10 unskilled workers (laborers) based on work ring and gender, the head of the IV division of PT Tebar Tandan Tenerah-Sampoerna Agro Tbk and the Village Head of Sidan. The data collection technique was done by means of observation, interview and documentation. The data analysis technique was carried out in 3 stages, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that PT Tebar Tandan Tenerah-Sampoerna Agro Tbk has carried out corporate social responsibility in the economic dimension in Sidan Village by assisting in economic development, building facilities and infrastructure, and having oil palm plantation business operations. The opening of job opportunities by PT Tebar Tandan Tenerah-Sampoerna Agro Tbk has an impact on increasing the income of the people of Sidan Village so that people can meet their daily needs such as food and education properly.Keyword: Community Income, Rough Workers (laborers), The existence of the company